The Role of Government in Illegal Fishing Prevention to Increase Fishermen's Economic Welfare in Aceh Province - Wahyuddin, Wahyuddin; Muksal, Muksal; Nirzalin, Nirzalin; Zulfikar, Zulfikar (SCAD Independent, 2019)
This research was conducted in order to assist the government to develop strategies and programs of poverty among fishermen in Aceh province. Aceh certainly has huge marine and fishery potentials, but the problem of fisherman poverty is still a major factor in the value of national poverty. The population of this research was fishermen in Nagan Raya, Pidie Jaya, Lhokseumawe, and Aceh Timur districts. Samples of the Active Fishermen are that society under the supervision of the Fisheries and Panglima Laot office. The results of this study indicate the lack of government's role in preventing illegal fishing hence there are still many illegal fishing cases that occur in the fisherman's area, causing fishermen not to get maximum results and make the fishermen always entangled into poverty conditions. Researchers recommend that the government should be able to solve the problems that exist in the scope of fishermen, especially the problem of illegal fishing, by adding programs that can improve the economic empowerment of fishermen so that fishermen do not just rely on catch but also have other side income so when fishermen do not get the catch expected, fishermen still have a stable income to support their daily life.